THE ROLE OF AGRICULTURE IN THE ECONOMIC DEVELOPMENT OF THE KHIV KHANATE - Matkarimova, Malika (Oriental Journal of History, Politics and Law, 2025)
The article is devoted to the role of agriculture in the economic development of the Khiva Khanate during the Kungirat dynasty. The article highlights the role of agriculture, farming, and animal husbandry in the economic development of the Khiva Khanate.